2003
DOI: 10.1099/mic.0.26108-0
|View full text |Cite
|
Sign up to set email alerts
|

Haemin uptake and use as an iron source by Candida albicans: role of CaHMX1-encoded haem oxygenase

Abstract: Candida albicans, unlike Saccharomyces cerevisiae, was able to use extracellular haemin as an iron source. Haemin uptake kinetics by C. albicans cells showed two phases: a rapid phase of haemin binding (with a K d of about 0?2 mM) followed by a slower uptake phase. Both phases were strongly induced in iron-deficient cells compared to iron-rich cells. Haemin uptake did not depend on the previously characterized reductive iron uptake system and siderophore uptake system. CaHMX1, encoding a putative haem oxygenas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 48 publications
(49 reference statements)
3
127
2
Order By: Relevance
“…We also included an additional 15 ironrelated genes that showed Cap2-dependent up-regulation (six genes) or down-regulation (nine genes), for which the L_H_Fe data were not available. Interestingly, eight of the 18 up-regulated genes in the CAP2/cap2⌬ data have been shown experimentally to be involved in iron uptake pathways, viz., SIT1 encoding siderophore transporter (72) , FET3, FTR1, FRP1, CFL5, and FRE9 encoding reductive iron uptake (73,74), and RBT5 and HMX1 being part of heme uptake (35,75,76) pathways (Fig. 4C).…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…We also included an additional 15 ironrelated genes that showed Cap2-dependent up-regulation (six genes) or down-regulation (nine genes), for which the L_H_Fe data were not available. Interestingly, eight of the 18 up-regulated genes in the CAP2/cap2⌬ data have been shown experimentally to be involved in iron uptake pathways, viz., SIT1 encoding siderophore transporter (72) , FET3, FTR1, FRP1, CFL5, and FRE9 encoding reductive iron uptake (73,74), and RBT5 and HMX1 being part of heme uptake (35,75,76) pathways (Fig. 4C).…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…It has been reported that hemin, one of the heme proteins, can be used as a source of iron [22,29]. Thus, antifungal activity induced in the mouse serum could be due to the restriction of use of iron originated from heme protein.…”
Section: Discussionmentioning
confidence: 99%
“…Y → H/PH switches are induced by temperatures between 35°C and 42°C [8,9], blood serum [10], hemoglobin at 1 mg/ml concentration (approximately 15.5 μM with 62 μM heme content; [11]), hemin (protoporphyrin IX with ferric ion or oxidized heme, which is released from hemoglobin; [12]) at 5-100 μg/ml (equals to 7.7-153.4 μM; [13]) or at 50 μM (equals to 32.6 μg/ml) concentrations [14], CO 2 [15,16], hypoxia + high CO 2 level [17], alkaline pH [15,18], the available carbon sources [8], and nitrogen starvation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Besides environmental factors, the acquisition of iron plays a central role in fungal metabolism and, therefore, it is considered as a key element in the invasion of host organisms by pathogenic fungi including C. albicans [14,27]. In the human body, iron is present exclusively in bound forms, e.g., in hemoglobin, transferrin, and ferritin [14,[27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation